2021
DOI: 10.3390/coatings11121537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Different Types of Aloin on Optical, Mechanical, and Antibacterial Properties of Waterborne Coating on Tilia europaea Surface

Abstract: The microcapsules were prepared by using melamine-formaldehyde resin as the wall material and aloin as the core material. The aloin was dissolved in ethanol and water to prepare microcapsules. The aloin powder, the aloin microcapsules prepared with ethanol as the solvent, and the aloin microcapsules prepared with water as the solvent were, respectively, added to the waterborne coating with different contents and coated on the surface of Tilia europaea. The effects of different modifiers and contents on the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A part of these components can be of interest for different applications considering their antimicrobial or optical properties and will be utilized in further studies. 21,22 Following the characterization of the original material, the cellulose extraction process was developed and the final powder obtained was first characterized by XRD, comparing its pattern to that of commercial MCC and to that of untreated waste, i.e., Aloe Peel powder (Figure 1a). As expected, the data show that Aloe Vera presents a similar pattern to commercial MCC, with crystallinity is of type I, and a high width at half height, suggesting that the isolated material possesses nanocrystalline domains.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A part of these components can be of interest for different applications considering their antimicrobial or optical properties and will be utilized in further studies. 21,22 Following the characterization of the original material, the cellulose extraction process was developed and the final powder obtained was first characterized by XRD, comparing its pattern to that of commercial MCC and to that of untreated waste, i.e., Aloe Peel powder (Figure 1a). As expected, the data show that Aloe Vera presents a similar pattern to commercial MCC, with crystallinity is of type I, and a high width at half height, suggesting that the isolated material possesses nanocrystalline domains.…”
Section: ■ Resultsmentioning
confidence: 99%
“…During the first step of the biomass treatment, Aloe powders were subjected to extraction using ethanol to remove lipidic fraction, chlorophylls, and the majority of anthraquinone species (AQs), which were then determined by HPLC analysis (Table ). A part of these components can be of interest for different applications considering their antimicrobial or optical properties and will be utilized in further studies. , …”
Section: Resultsmentioning
confidence: 99%
“…Anthranoids Aloin [77] NF Soluble [82] 5.51 to 6.60% [83] 418.4 and 148 • C Decreased serum glucose and significantly increased serum insulin levels. It was shown that serum levels of MDA and SOD were significantly decreased, while blood GSH was significantly increased as compared to diabetic rats.…”
Section: Glycosidesmentioning
confidence: 99%
“…Bacteria attached to the coating surface can cause damage, leading to a decrease in its protective ability against wooden substrates [25,26]. Adding an active ingredient with an antibacterial effect into the coating can make the coating antibacterial [27] and protect the MDF [28]. The coatings with antibacterial microcapsules can protect the coating and optimize the living environment.…”
Section: Of 23mentioning
confidence: 99%